Basic mechanisms of afwillite seeding for acceleration of tricalcium silicate hydration. (June 2020) - Bellmann, F.; Sowoidnich, T.; Horgnies, M.; Gartner, E.
Abstract: Afwillite is a crystalline calcium silicate hydrate (3CaO·2SiO2 ·3H2 O) that can be used for the acceleration of tricalcium silicate hydration. Experimental data was recorded in this study to shed further light on the basic mechanisms for this acceleration effect. It is observed that afwillite addition favours growth of the afwillite seeds and hardly any C-S-H is formed. The pore solution chemistry during hydration closely resembles that of unseeded tricalcium silicate indicating that pore solution chemistry is not triggering the accelerating effect of afwillite. Much higher degrees of hydration are observed after the main hydration period in the presence of afwillite seeds. This is explained by the formation of relatively large afwillite crystals in some distance to the surface of tricalcium silicate. This is different to the hydration of tricalcium silicate in the absence of afwillite seeds when C-S-H is precipitated on the surface of the tricalcium silicate particles.